PERANCANGAN WEBSITE UNTUK PERKUMPULAN ORANG TUA DENGAN ANAK DISABILITAS INDONESIA (PORTADIN) - Tony; Arya Wira Kristanto; Lely Hiryanto (Jurnal Serina Abdimas, 2025)
Portadin, an organization that was founded in 2005 and officially launched nationally in 2011, acts as a forum for parents of children with disabilities. This organization carries out important tasks in child protection, while also functioning as an information center, empowerment tool, government partner, and advocacy facilitator. However, Portadin faces challenges in expanding its reach and improving its professionalism. The lack of a centralized and easily accessible digital platform is a major obstacle in disseminating information, documenting activities, and facilitating communication. As a result, Portadin has difficulty reaching more members, interacting with the wider community, and strengthening its professional image. To overcome this problem, the PKM implementation team has taken the initiative to develop an official Portadin website using WordPress, which is now available at https://portadin.org/. The website is designed with five main menus—Home, About, News, Activities, and Contact—which have gone through a process of design, development, and testing. The existence of this website will expand the reach and improve the professionalism of Portadin. Further, to ensure sustainable use of the website, the PKM team will prepare a management manual and conduct training for Portadin administrators. This step aims to enable Portadin to independently update content and information, facilitate effective communication with members and the public, and function as a more modern and easily accessible information center. ABSTRAK Portadin, organisasi yang berdiri sejak tahun 2005 dan diresmikan secara nasional pada 2011, berperan sebagai wadah bagi orang tua anak disabilitas. Organisasi ini mengemban tugas penting dalam perlindungan anak, sekaligus berfungsi sebagai pusat informasi, sarana pemberdayaan, mitra pemerintah, dan fasilitator advokasi. Namun, Portadin menghadapi tantangan dalam memperluas jangkauan dan meningkatkan profesionalismenya. Kurangnya platform digital yang terpusat dan mudah diakses menjadi hambatan utama dalam menyebarkan informasi, mendokumentasikan kegiatan, dan memfasilitasi komunikasi. Akibatnya, Portadin kesulitan menjangkau lebih banyak anggota, berinteraksi dengan masyarakat luas, dan memperkuat citra profesionalnya. Untuk mengatasi permasalahan ini, tim pelaksana PKM telah berinisiatif mengembangkan website resmi Portadin menggunakan WordPress, yang kini tersedia di https://portadin.org/. Website ini dirancang dengan lima menu utama—Beranda, Tentang, Berita, Kegiatan, dan Kontak—yang telah melalui proses perancangan, pengembangan, dan pengujian. Keberadaan website ini akan memperluas jangkauan dan meningkatkan profesionalisme Portadin. Lebih lanjut, untuk memastikan pemanfaatan website yang berkelanjutan, tim PKM akan menyusun manual pengelolaan dan menyelenggarakan pelatihan bagi pengurus Portadin. Langkah ini bertujuan agar Portadin dapat secara mandiri memperbarui konten dan informasi, memfasilitasi komunikasi yang efektif dengan anggota dan masyarakat, serta berfungsi sebagai pusat informasi yang lebih modern dan mudah diakses.